The interaction patterns of pandemic-initiated online teaching: How teachers adapted. (April 2022) - Le, Van Thinh; Nguyen, Ngan Ha; Tran, Tran Le Nghi; Nguyen, Luan Thanh; Nguyen, Thi Anh; Nguyen, Minh Trang
Abstract: This study investigated how teachers adjusted their teaching practices for online teaching during the COVID-19 pandemic in Vietnam. In the study, we collected data from ten teachers within the Department of English at a university in Vietnam through semi-structured interviews via Zoom. During the interviews, the participants shared how they organised their teaching activities and addressed challenges in engaging students. To analyse the data, we focused on the variety of interaction patterns (teacher-student, student-student and student-content) in online teaching. The results showed that most of the teachers deployed activities for two main types of interaction: teacher-student, and student-content, but not for student-student interaction. Teachers also reported that they received limited online teacher training and had to learn by themselves how to engage students remotely. While the university tried to support teachers, no consistent online teaching guidelines were provided. The study suggests that higher education institutions should offer training opportunities and provide teachers with clear guidelines for online teaching.